Analisis Strategi Negosiasi China Terhadap Upaya Normalisasi Saudi-Iran 2023 - Dina Hikmatu Zahra; Agussalim Burhanuddin (Lembaga Pengembangan Kinerja Dosen, 2024)
. An analysis of China’s negotiating strategy toward Saudi Arabia and Iran’s efforts to normalize relations highlights China’s important role as a mediator in resolving the long-standing and complex rivalry between the two countries. Geopolitical, economic, and diplomatic factors underpin China’s strategy to minimize conflict and promote regional stability. Through its multilateral approach, economic cooperation, balancing interests, and focus on energy, China has played a key role in facilitating dialogue and reaching an agreement between Saudi Arabia and Iran. By maintaining its position as a neutral and respected mediator, China has the potential to strengthen economic and diplomatic ties in the region and promote peace and stability in the Middle East.